Vitamin C deficiency in Australian hospitalised patients: an observational study. Issue 2 (12th February 2019) - Sharma, Yogesh; Miller, Michelle; Shahi, Rashmi; Doyle, Adrienne; Horwood, Chris; Hakendorf, Paul; Thompson, Campbell
Abstract: Background: Vitamin C has anti‐oxidant properties and acts as a cofactor for several enzymes. Hypovitaminosis C has been associated with bleeding, endothelial dysfunction and death. The prevalence of hypovitaminosis C is unknown in Australian hospitalised patients, and its clinical relevance is uncertain. Aims: To determine the prevalence, characteristics and clinical outcomes of hospitalised patients with hypovitaminosis C. Methods: This observational study included general‐medical inpatients in a tertiary‐level hospital in Australia. High‐performance liquid chromatography (HPLC) was used to determine plasma vitamin C levels. As per Johnston's criteria, vitamin C levels of ≥28 μmol/L were classified as normal and <28 μmol/L as low. Clinical outcomes determined included length of hospital stay (LOS), nosocomial complications, intensive care unit admission and in‐hospital mortality. Results: A total of 200 patients participated in this study, and vitamin C levels were available for 149 patients, of whom 35 (23.5%) had normal vitamin C levels, and 114 (76.5%) had hypovitaminosis C. Patients with hypovitaminosis C were older and had higher C‐reactive protein (CRP) levels. Median LOS was 2 days longer in patients with hypovitaminosis C (6 days (interquartile range (IQR) 4, 8) vs 4 days (IQR 3, 6), P = 0.02), and they had fourfold higher odds of staying in hospital for >5 days than those with normal vitamin C levels. Other clinical outcomes were similar between the two groups. Conclusions: Hypovitaminosis C is common in hospitalised patients and is associated with prolonged LOS. Further research is needed to ascertain the benefits of vitamin C supplementation in vitamin C‐depleted patients.